PEMBERDAYAAN PETANI MUTIARA DI DESA SEKAROH KECAMATAN JEROWARU LOMBOK - -, Mustami’uddin; Zuryani, Nazrina; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 01 (2021): JISSOROT, 2021)
Lombok Island as one of the suppliers of pearl needs which has decreased productivity requires community empowerment, especially for pearl farmers. Empowerment of pearl farming communities in Sekaroh Village has been ongoing since 2013. Community empowerment in Sekaroh Village includes 6 aspects of empowerment. The aspects consist of environmental, cultural, economic, social, political and personal aspects. However, because of the constraints of funding and infrastructure and limited resources, it is an obstacle to the empowerment program. This has implications for the six aspects of empowerment that have not been achieved optimally so that good coordination is needed between pearl farmers, PT Autore as the private sector and the local government as policy makers to create a good and profitable business climate for all parties.   Keywords: Community Empowerment, Mutiara Farmers, Community Development